Effect of Honey Cinnamon Vaginal Cream and Clotrimazole Vaginal Cream on Improvement of Candida Vaginitis Symptoms in Women: Randomized Clinical Trial - Tayebeh Rasooli; Fatemeh Nahidi; Faraz Mojab; Malihe Nasiri; Hamideh Parsapour (Mashhad University of Medical Sciences, 2019)
Introduction: Vaginitis candidiasis is one of the common causes of women's referral to health centers, which disrupts the patient's quality of life. Considering the antifungal effects of honey and cinnamon and the tendency to use medicinal plants and natural substances, this study was performed with aim to investigate the effect of honey cinnamon vaginal cream on the improvement of candida vaginitis symptoms. Methods: This triple-blind randomized clinical trial was conducted on 100 patients in Hamedan during 2018. Patients with clinical complaints of vaginal discharge, burning and itching with a positive culture for vaginitis candidiasis were divided into two groups of honey cinnamon vaginal cream and clotrimazole vaginal cream (n=50 in each group). One week after treatment, the patients were assessed through examination and culture. The research tools were information forms and a checklist of clinical observations, microscope, pH paper, and culture medium. Data were analyzed by SPSS software (version 20) and independent t-test, Mann-Whitney, Chi-square, Fisher exact, and McNemar test. P< 0.05 was considered statistically significant. Results: In both groups, the symptoms improved after treatment compared to pre-treatment (P <0.001). In honey cinnamon vaginal cream group, burning was significantly less than the clotrimazole group (P = 0.008). The culture results of the two groups were similar after treatment (P=0.461). Conclusion: The honey cinnamon vaginal cream was effective in improving the symptoms of vaginitis candidiasis and it can be advisable to use it as an alternative to the clotrimazole vaginal cream.